Allergic and non-allergic skin diseases in children of Ukraine: a retrospective study of the prevalence and incidence over the past 24 years - Volosovets , O.P.; Bolbot , Yu.K.; Beketova , G.V.; Berezenko , V.S.; Umanets , T.R.; Rechkina , O.O.; Міtiuriaeva-Korniyko, I.O.; Volosovets , T.М.; Pochinok, T.V. (Medicni Perspektivi, 2021)
Bacterial, allergic, parasitic and fungal skin lesions are much more common among children than among adult patients. The aim of this study was to analyze data on the prevalence and incidence of diseases of skin and subcutaneous tissue with allergic and non-allergic origin among children of Ukraine in period from 1994 to 2017. Our main purpose was to determine the possible impact of different adverse environmental factors on children`s growth, including radiation, connected with the Chernobyl disaster in 1986. Over the past 24 years Ukraine has witnessed a 10.3% increase in prevalence of diseases of skin and subcutaneous tissue among children and 8.6% raise of incidence rate with a predominance of detection of this pathology in children affected by the Chernobyl accident and children from areas of radiological control. We have found a direct influence of moderate strength on the connection between population-weighted effective dose of total human exposure (in millizieverts) in different regions of the country in the period of 1997-2011 and the incidence and prevalence of skin diseases among children aged 0-14 years, including 2011 (p<0.05).This fact may indicate the impact of this disaster on the occurrence and pathogenesis of skin diseases and its consequences among children. During the same period, due to the influence of a number of environmental factors, there was a significant transformation in the structure of skin diseases in children. We have witnessed double increasing of the proportion of allergic lesions of the skin and its elements. The prevalence of diseases of the skin and its elements in general has reached 28.7% against the corresponding reduction of skin infections.